Disentangling Ethnic and Contextual Influences Among Parents Raising Youth in High-Risk Communities - Hurley, Sean (2008)
This article reports on analyses examining contextual influences on parenting with an ethnically and geographically diverse sample of parents (predominantly mothers) raising 387 children (49% ethnic minority; 51% male) in high-risk communities. Parents and children were followed longitudinally from first through tenth grades. Contextual influences included geographical location, neighborhood risk, SES, and family stress. The cultural variable was racial socialization. Parenting constructs created through the consensus decision-making of the Parenting Subgroup of the Study Group on Race, Culture, and Ethnicity (see Le et al., 2008) included Monitoring, Communication, Warmth, Behavioral Control and Parenting Efficacy. Hierarchical regressions on each parenting construct were conducted for each grade for which data were available. Analyses tested for initial ethnic differences and then for remaining ethnic differences once contextual influences were controlled. For each construct, some ethnic differences did remain (Monitoring, ninth grade; Warmth, third grade; Communication, kindergarten; Behavioral Control, eighth grade; and Parenting Efficacy, kindergarten through fifth grade). Ethnic differences were explained by contextual differences in the remaining years. Analyses examining the impact of cultural influences revealed a negative relation between racial socialization messages and Communication or Monitoring.